Circumstances of infection with HCV in selected Polish provinces - Lidia Sierpińska (Kazimierz Wielki University, 2021)
Introduction. In Poland, approximately 730,000 people are infected with hepatitis C virus (HCV), which is nearly 2% of the total population, and about 170 million worldwide - 3% of the global population.  Approximately 70-80% people infected with hepatitis C virus develop chronic hepatitis. Knowledge of the circumstances associated with the risk of infection with HCV is very important in the prophylaxis of hepatitis C.    Materials and Method. The study was conducted during August 2014 - May 2018 in            a group of 220 patients infected with HCV by the method of a diagnostic survey, using an author-constructed questionnaire. Results. The majority of respondents (138; 62.7%) did not know the circumstances of infection with HCV, whereas more than 1/3 of them (82; 37.3%) had knowledge concerning their infection. The respondents reported that the infection could have been mainly associated with a surgical procedure, followed by blood transfusion. The remaining circumstances of infection were: dental treatment, childbirth, organ transplantation, dialysis, treatment in a conservative ward, occupational exposure, plasmapheresis, as well as tattoo and narcotic injection. Self-reported state of respondents' knowledge concerning hepatitis C was mainly on the mean level (160; 72.7%). About ¾ of respondents (173; 78.6%) did not consider themselves to be disabled due to hepatitis C. Conclusions. Health education is recommended in the population of adults about the risk of contracting HCV in treatment facilities and other places, where there is the transmission of blood-borne infections, as well as concerning the essence of chronic hepatitis C.